(untitled) (Journal of history-rus, 2021)
The horse branding has deep roots. Some scholars refer the origin of tamga-like signs to the period of сlan system. Some researchers associate their origin with the era of formation and development of pastoral nomadism. In the Middle Ages the Turkic and other peoples of the Eurasian steppes used the horse marking as a sign of ownership. They were applied on the neck under the mane, on the hoof, on the back slightly above the saddle, on the left or right thigh, on the cheek, in rare cases behind the elbow (with the aim to hide tamga) by using a special hot-iron. There is information about temporary branding (by painting or haircuts) for horses, intended for sale or exchange. There is one more sign of distinction for horses – “en”. “En ” and “tamga” are equivalent categories. One of the most reliable evidences of horse branding are petroglyphs of the Middle Ages. The horse branding topic is mentioned in written sources of 5th c. BC. According to the researchers, tamgas on horses among the medieval rock carvings are comparable in appearance to the signs found in Mongolia and the Altai Mountains. The horse branding is a common phenomenon for all Turkic peoples. The continuity of some tamgas has been under observation since ancient Turkic times. In our time, this tradition has undergone signifi- cant changes. Key words: Turks, Middle Ages, tamga, sign, symbol, tamga studies, horse branding, Kazakh steppes.